The effect of the concentration of jakaba and biosaka liquid organic fertilizers on the growth and yield of purple eggplant (Solanum melongena L.) variety F1 mustang - Supriana Supriana; Andi Apriany Fatmawaty; Kiki Roidelindho; Dewi Firnia (Jurnal Agrotek Ummat, 2026)
Purple eggplant (Solanum melongena L.) is a horticultural commodity with high economic value, whose production in Banten Province fluctuates due to low soil nutrient content. This study aims to analyze the effect of Jakaba Liquid Organic Fertilizer (POC) concentration and Biosaka solution on the growth and yield of purple eggplant. The Research method used a factorial Randomized Block Design (RBD) with two factors. The first factor was the concentration of Jakaba POC (J0: 0, J1: 20, J2: 40, J3: 60 ml/l). The second factor was the concentration of Biosaka (B0: 0%, B1: 25%, B2: 50%, B3: 75%). There were 16 treatment combinations with three replicates. The observation parameters consisted of plant height, number of leaves, number of fruits per plant, and fruit weight per plant. The results showed that a Jakaba concentration of 40 ml/l (J2) had a significant effect on plant height (11.33 cm at 3 WAT and 26.72 cm at 4 WAT), leaf number (9.08 leaves at 4 WAT), and fruit number (average of 2.25 fruits). The concentration of Biosaka 75% (B3) gave the best results in plant height (8.48 cm at 2 WAT and 27.34 at 4 WAT), number of leaves (7.67 leaves at 3 WAT and 8.75 leaves at 4 WAT), and fruit weight (152.86 grams). A significant interaction occurred between Jakaba 40 ml/l and Biosaka 75% (J2B3) on plant height (31.50 cm) and number of leaves (10.33 leaves) at 4 WAT.